2013
DOI: 10.1016/j.bbrc.2013.10.072
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial fatty acid synthesis (mtFASII) pathway is capable of mediating nuclear-mitochondrial cross talk through the PPAR system of transcriptional activation

Abstract: Mammalian cells contain two fatty acid synthesis pathways, the cytosolic FASI pathway, and the mitochondrial FASII pathway. The selection behind the conservation of the mitochondrial pathway is not completely understood, given the presence of the cytosolic FAS pathway. In this study, we show through heterologous gene reporter systems and PCR based arrays that overexpression of MECR, the last step in the mtFASII pathway, causes modulation of gene expression through the PPAR pathway. Electromobility shift assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Overall, our here presented findings displayed that the upregulation of both pathways occurs in parallel to the changes in muscle fiber type. It has recently been shown that MECR, one protein of the mFASII pathway, regulates gene expression via PPARa and PPARc signaling and modulates the abundance of bioactive lipids [48,49]. Therefore, a role of this pathway in metabolic regulation cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our here presented findings displayed that the upregulation of both pathways occurs in parallel to the changes in muscle fiber type. It has recently been shown that MECR, one protein of the mFASII pathway, regulates gene expression via PPARa and PPARc signaling and modulates the abundance of bioactive lipids [48,49]. Therefore, a role of this pathway in metabolic regulation cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The genes associated with MECR were found enriched for adipogenesis, adipocytokine signaling, fatty acid biosynthesis, PPAR signaling and pathways in cancer. MECR associated genes have been found affected in cancer while MECR is reported as the last step gene of fatty acid biosynthesis pathway, seated at mitochondria, but also standing as the final connecter to the nuclear signal through PPAR ( 58 ). Another target gene, MRTO4 , is associated with ribosome formation and translation rate, which was reported to be involved with PKR to control the cell cycle process in normal conditions ( 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…MECR is involved in mitochondrial fatty acid synthesis and it was shown that over-expression of this gene increases Peroxisome proliferator-activated receptor alpha (PPARα) activity. 8 PPARα can in turn down-regulate expression of pro-inflammatory genes and is localized in bronchial T-, B-and epithelial cells. 9 In a rat emphysema model, treatment with a PPARα-γ agonist reduced apoptosis of the alveolar cells and halted progression of emphysema.…”
Section: Fvcmentioning
confidence: 99%